Warm-up exercises based on variability - Vilches, F. (Coaching and Sport Science Review, 2021)
The proper structuring of the content to be developed in a tennis session is one of its most important aspects. Within this structure, the warm-up is a part that should always be present. Despite its importance, on many occasions, the warm-up does not receive from the coaches all the attention it should. The present article proposes a number of methodological tools based on variability training principles with the aim of providing greater specificity and quality to the tennis warm-up.